Repo market effects of the term securities lending facility - Michael J. Fleming; Warren B. Hrung; Frank M. Keane (Federal Reserve Bank of New York, 2010)
The Term Securities Lending Facility (TSLF) was introduced by the Federal Reserve to promote liquidity in the financing markets for Treasury and other collateral. We evaluate one aspect of the program - the extent to which it has narrowed repo spreads between Treasury collateral and less liquid collateral. We find that TSLF operations have precipitated a significant narrowing of repo spreads. More refined tests indicate the market conditions and types of operations associated with the program's effectiveness. Various additional tests, including a split-sample test, suggest that our findings are robust.
Keywords: G12; G14; E52; E58; E43; 330; Federal Reserve; liquidity facility; repo market; repurchase agreement; Geldpolitik; Schatzpapier; Offenmarktpolitik; USA